2020
DOI: 10.3389/fcell.2020.608308
|View full text |Cite
|
Sign up to set email alerts
|

FK506 Induces the TGF-β1/Smad 3 Pathway Independently of Calcineurin Inhibition to Prevent Intervertebral Disk Degeneration

Abstract: BackgroundIntervertebral disk (IVD) degeneration is the most common cause of lower back pain. Inhibiting inflammation is a key strategy for delaying IVD degeneration. Tacrolimus (FK506) is a potent immunosuppressive agent that is also beneficial to chondrocytes via alleviating inflammation. However, the potential function of FK506 in IVD and the underlying mechanisms remain unknown. The current study is aim at exploring the underlying mechanism of FK506 in preventing IVD degeneration.MethodsCell morphology was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Hyperosmotic culture has recently been shown to have similar effects on cell types from other skeletal tissues, such as the nucleus pulposus cells from the intervertebral disk (IVD) [12,13]. Indeed, a recent report suggested that FK506 induces the TGF-β1/SMAD3 pathway independently of Cn inhibition to prevent IVD degeneration [77]. This is largely in agreement with our results showing that FK506, but not CsA, induces Acan expression.…”
Section: Discussionsupporting
confidence: 92%
“…Hyperosmotic culture has recently been shown to have similar effects on cell types from other skeletal tissues, such as the nucleus pulposus cells from the intervertebral disk (IVD) [12,13]. Indeed, a recent report suggested that FK506 induces the TGF-β1/SMAD3 pathway independently of Cn inhibition to prevent IVD degeneration [77]. This is largely in agreement with our results showing that FK506, but not CsA, induces Acan expression.…”
Section: Discussionsupporting
confidence: 92%
“…Although there are complex and multifactorial causes for the development of LBP, it is widely accepted that IVDD is the major contributor to LBP [ 19 ]. IVDD can be affected by both genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the degradation of the ECM is also an important factor driving the progression of IVDD ( 27 ). The ECM is a non-cellular 3D macromolecular network composed of collagen, proteoglycans/glycosaminoglycans, elastin, fibronectin, laminin and several other glycoproteins ( 28 ).…”
Section: Discussionmentioning
confidence: 99%